Traditional Chinese medicine formula 01 for nasopharyngeal carcinoma (NPC01) for head & neck cancer and health-related quality of life: a retrospective study - Li Yanwei; He Feng; Wang Xudong; Pan Zhanyu (BMC, 2022)
Abstract Background The traditional Chinese medicine (TCM) formula 01 for nasopharyngeal carcinoma (NPC01) is used in the management of head and neck cancers (HNCs), but whether NPC01 has an impact on the HR-QOL of patients with HNCs is unknown. Methods This was a retrospective study of patients with HNCs who were treated between January 2019 and January 2020 at the Head & Neck Cancer Center of Tianjin Medical University Cancer Institute & Hospital. The patients were grouped according to whether they received NPC01 or not (controls). All patients routinely completed the EORTC QLQ-C30 and QLQ-H&N35 modules before and after 3 months of systemic treatment. Health economics were collected. Results The patients who received NPC01 were older than the controls (48.6 ± 11.4 vs. 43.4 ± 8.8 years, P = 0.004). All other characteristics were comparable between the two groups (all P > 0.05). In EORTC QLQ-C30, physical functioning (P = 0.03), fatigue (P = 0.04), pain (P = 0.02), appetite loss (P = 0.02), and constipation (P = 0.01) scores were improved more in the NPC01 group than in controls. In EORTC H&N35, the scores for pain (P = 0.02), swallowing (P = 0.01), and dry mouth (P = 0.02) were better in the NPC01 group than in controls. The NPC01 cost was 38.94 RMB/patient compared with 12.81 RMB/patient for regular follow-up, but considering insurance coverage, the financial burden was not higher. Conclusions The results suggest that NPC01 improves HNCs-related symptoms and HR-QOL.